Biologic Evaluation of a Heterodimeric HER2-Albumin Targeted Affibody Molecule Produced by Chemo-Enzymatic Peptide Synthesis - Yongsheng Liu; Rezan Güler; Yunqi Liao; Anzhelika Vorobyeva; Olof Widmark; Theodorus J. Meuleman; Anna Koijen; Leendert J. van den Bos; Robert Naasz; Vitalina Bodenko; Anna Orlova; Caroline Ekblad; et al. (Pharmaceutics, 2022)
Targeted molecular radiation therapy is a promising emerging treatment modality in oncology, and peptide synthesis may shorten the time to reach the clinical stage. In this study, we have explored Chemo-Enzymatic Peptide Synthesis, or CEPS, as a new means of producing a therapeutic HER2 targeted Affibody® molecule, comprising a C-terminal albumin binding domain (ABD) for half-life extension and a total length of 108 amino acids. In addition, a DOTA moiety could be incorporated at N-terminus directly during the synthesis step and subsequently utilized for site-specific radiolabeling with the therapeutic radionuclide 177Lu. Retained thermodynamic stability as well as retained binding to both HER2 and albumin was verified. Furthermore, HER2 binding specificity of the radiolabeled Affibody molecule was confirmed by an in vitro saturation assay showing a significantly higher cell-bound activity of SKOV-3 (high HER2 expression) compared with BxPC3 (low HER2 expression), both in the presence and absence of HSA. In vivo evaluation in mice bearing HER2 expressing xenografts also showed specific tumor targeting as well as extended time in circulation and reduced kidney uptake compared with a HER2 targeted Affibody molecule without the ABD moiety. To conclude, we have demonstrated that CEPS can be used for production of Affibody-fusion molecules with retained in vitro and in vivo functionality.